Studi Kasus Penerepan Prinsip Manajemen Bisnis Islam dalam Industri Yoghurt - Komalasari, Mela; Afghani, Muhammad Fadiar; Chatelia, Naila; Salam, Mochamad Fadlani (Bayani, 2025)
The food and beverage industry is a strategic sector that plays a crucial role in the economy and fulfilling societal needs. One of the fastest-growing products is yogurt, particularly due to the rising awareness of a healthy lifestyle. In Indonesia, as a country with a Muslim-majority population, halal compliance is a fundamental factor in yogurt production and marketing. This study aims to analyze the application of Islamic business management principles in the sharia-based yogurt industry, with a case study on Dapur Kefir Bandung. This research employs a qualitative case study method. Data were collected through in-depth interviews and direct observations to explore how Islamic principles are integrated into production, human resource management, finance, and marketing. The findings reveal that Dapur Kefir Bandung has successfully implemented Islamic business principles, including halal raw materials, financial transparency, and fairness in employee and consumer relations. The company is also actively engaged in social responsibility programs, such as donations and consumer education on the importance of halal food. However, the main challenges in developing this industry include consumer awareness, market competition, and the complex halal certification process. With a consistent Islamic management strategy, the sharia-based yogurt industry has significant growth potential in the Indonesian market.